Within-subject variation in hemoglobin mass in elite athletes - Eastwood, A.; Sharpe, K.; Bordon, P.; Woolford, S. M.; Saunders, P. U.; Robertson, E. Y.; Clark, S. A.; Gore, C. J. (Medicine & Science in Sports & Exercise, 2012)
ABSTRACT Illicit autologous blood transfusion to improve performance in elite sport is currently undetectable, but the stability of longitudinal profiles of an athlete`s hemoglobin mass (Hbmass) might be used to detect such practices.